2020
DOI: 10.1007/s10551-020-04663-6
|View full text |Cite
|
Sign up to set email alerts
|

How Much You See Is How You Respond: The Curvilinear Relationship Between the Frequency of Observed Unethical Behavior and The Whistleblowing Intention

Abstract: This article uses a sample of 3076 employees working in the USA to examine the relationship between the frequency of unethical behavior that employees observe in their organization and their intention to whistleblow. The results confirm the expected curvilinear relationship based on the Focus Theory of Normative Conduct. This relationship is a combination of a diminishing negative relationship between the frequency of observed unethical behavior and the intention to whistleblow internally and a linear positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 95 publications
1
2
0
4
Order By: Relevance
“…Previous studies have shown that highly rated ESG firms have an above-average risk management and control mechanism in place (Galbreath, 2013), which helps companies conduct morally reflective decision-making in their strategic and day-to-day business, and abate unethical practices (Kaptein, 2020). Therefore, it is reasonable to assume that ESG-rated IPOs experience less frequent incidents, such as industrial accidents, fraud or corruption cases, which can make society retract their legitimacy.…”
Section: Esg and Idiosyncratic Risk Of Iposmentioning
confidence: 99%
“…Previous studies have shown that highly rated ESG firms have an above-average risk management and control mechanism in place (Galbreath, 2013), which helps companies conduct morally reflective decision-making in their strategic and day-to-day business, and abate unethical practices (Kaptein, 2020). Therefore, it is reasonable to assume that ESG-rated IPOs experience less frequent incidents, such as industrial accidents, fraud or corruption cases, which can make society retract their legitimacy.…”
Section: Esg and Idiosyncratic Risk Of Iposmentioning
confidence: 99%
“…As organizações solicitam em seus códigos de conduta e políticas que os funcionários denunciem comportamentos antiéticos e, em alguns casos, os definem como corresponsáveis por desvios de conduta conhecidos e não reportados. Alguns autores compreendem a denúncia como um comportamento social positivo (Miceli;Near, 1994), como um comportamento altruísta (Dozier;Miceli, 1985), como lealdade à sociedade (Andrade, 2015), como compromisso moral (Kaptein, 2022).…”
Section: Comportamento Moral éTica Organizacional E O Papel Das Denún...unclassified
“…A relação entre a observação de condutas antiéticas e a intenção de delação foi estudada por Kaptein (2022) e mostrou um aspecto sensível no que tange à construção de significados. Por meio de pesquisa empírica, observou-se que no caso das denúncias internas, quanto maior a observação da frequência de comportamentos inadequados, menor a intenção de realizar denúncias, justamente porque o funcionário entende que a conduta é normalizada no ambiente organizacional.…”
Section: Entre a Responsabilidade E A Vulnerabilidade Do Denuncianteunclassified
See 2 more Smart Citations